Biodegradable Chitosan-Based Films as an Alternative to Plastic Packaging - Natalia Wrońska; Nadia Katir; Marta Nowak-Lange; Abdelkrim El Kadib; Katarzyna Lisowska (Foods, 2023)
The impact of synthetic packaging on environmental pollution has been observed for years. One of the recent trends of green technology is the development of biomaterials made from food processing waste as an alternative to plastic packaging. Polymers obtained from some polysaccharides, such as chitosan, could be an excellent solution. This study investigated the biodegradability of chitosan–metal oxide films (ZnO, TiO2, Fe2O3) and chitosan-modified graphene films (CS-GO-Ag) in a soil environment. We have previously demonstrated that these films have excellent mechanical properties and exhibit antibacterial activity. This study aimed to examine these films’ biodegradability and the possibility of their potential use in the packaging industry. The obtained results show that soil microorganisms were able to utilize chitosan films as the source of carbon and nitrogen, thus providing essential evidence about the biodegradability of CS, CS:Zn (20:1; 10:1), and CS:Fe2O3 (20:1) films. After 6 weeks of incubation, the complete degradation of the CS-Fe2O3 20:1 sample was noted, while after 8 weeks, CS-ZnO 20:1 and CS-ZnO 10:1 were degraded. This is a very positive result that points to the practical aspect of the biodegradability of such films in soil, where garbage is casually dumped and buried. Once selected, biodegradable films can be used as an alternative to plastic packaging, which contributes to the reduction in pollution in the environment.